(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The essay analyses Hemingway’s short stories by saying that they are eco-conscious. The analysis demonstrates a conflicting characteristic of Hemingway’s normal love and aggression. His approach to existence is thus paradoxical. The protagonists are distressed and shift to nature for warmth and solace. By explaining existence, the protagonist’s emotions and feelings are reflected. The results indicate that the short stories of Hemingway are abundantly environmental. His novels and novels, published after the short stories, often have the same ecological problems. This paper concludes that the short stories of Hemingway demonstrate ecological holism.